PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI, DAN KUALITAS PELAYANAN TERHADAP PENGGUNAAN SISTEM DAN KEPUASAN PENGGUNA SISTEM SERTA PENGARUH PENGGUNAAN SISTEM DAN KEPUASAN PENGGUNA SISTEM TERHADAP NET BENEFIT SIPKD (STUDI PADA OPD KABUPATEN WONOGIRI) - Darmawan Wahidul Ikhsani; Muhammad Yusuf (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
The purpose of this research is to know the impact of the utilization of SIPKD on Wonogiri Regency OPD by using DeLone and McLean model as a whole. Variables used in this research are system quality, information quality, service quality, system usage, system user satisfaction and net benefit of SIPKD. Population is OPD in Wonogiri Regency. The sample of this research is employee from 25 OPD in Wonogiri Regency. The selected respondents were those using SIPKD. Data were collected through questionnaires and analyzed using PLS analysis. Based on the tests conducted obtained the results that the system quality, information quality and service quality positively affect the system usage. Then the information quality and service quality positively affect the system user satisfaction while the system quality has no positive effect on the system user satisfaction. The system usage does not positively affect the net benefit of SIPKD, while system user satisfaction positively affects the net benefit of SIPKD. The result of R-square variable of system usage is 58,9%, R-square variable of system user satisfaction is 39,8% and R-square variable net benefit of SIPKD is 36,8%.